Two new 28-nor-oleanane-type triterpene saponins from roots of Camellia oleifera and their cytotoxic activity. Issue 7 (2nd July 2016) - Zhang, Zi-Yu; Wu, Jiang-Ping; Gao, Bin-Bin; Ren, Hai-Tao; Liu, Yan-Li; Li, Xiao-Ran; Li, Kun-Ping; Xu, Qiong-Ming; Yang, Shi-Lin
Abstract: Two new 28-nor-oleanane-type triterpene saponins, oleiferoside U (1 ), and oleiferoside V (2 ) were isolated from the 50% EtOH extract of the roots of Camellia oleifera C. Abel. Their structures were elucidated as camellenodiol 3 β - O - β -d -galactopyranosyl-(1→2)- β -d -xylopyranosyl-(1→2)-[ β -d -galactopyranosyl-(1→3)]- β -d -glucuronopyranoside and camellenodiol 3 β - O - β -d -galactopyranosyl-(1→3)- β -d -xylopyranosyl-(1→2)-[ β -d -galactopyranosyl-(1→3)]- β -d -glucuronopyranoside. Their chemical structures were established mainly on the basis of integrated spectroscopic techniques. In vitro, cytotoxic activities of the two new triterpene saponins were evaluated against three human tumor cell lines (A549, SMMC-7721, and MCF-7) using the MTT assay. Both of them showed a certain cytotoxic activities toward the tested cell lines and gave IC50 values in the range of 45.04–63.22 μM.